Compound crystal form as well as preparation method and application thereof
By preparing nucleoside compounds with specific crystal forms, the difficulty in controlling the purity of phosphoramidite monomers and the easy water absorption of protective nucleosides are solved, achieving higher purity and yield, and the compounds in this crystal form are easy to store.
Patent Information
- Application Number
- CN202411309848.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the purity control of the phosphoramidite monomer is difficult, and the protective nucleoside is mostly amorphous solid powder, which easily absorbs water and affects the purity and yield of the product.
Provided is a compound with a specific crystal form and a preparation method thereof. The crystal form of the compound is obtained by mixing with a crystallization solvent, heating to dissolve, and cooling to crystallize. The characteristic peak 2θ of the X-ray powder diffraction pattern of this crystal form includes a specific angle range, and acetonitrile and/or ethyl acetate is used as the crystallization solvent.
The nucleoside crystal prepared by this method is not easy to deteriorate. It has higher melting points, low water content and diversion, and it is easy to save, and it helps improve the purity and yield of the phosphoricide monomer.
Smart Images

Figure CN119350414A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of medical technology, and in particular to a compound crystal form and a preparation method and application thereof. Background Art
[0002] Nucleic acid drugs, as the third largest type of drugs after small molecule drugs and antibody drugs, have become a global focus and hotspot for biopharmaceutical companies. Currently, there are 14 small nucleic acid drugs approved for marketing worldwide. As a key material for the synthesis of nucleic acid drugs, the purity control of phosphoramidite monomers is very important. The supply of nucleoside monomers that meet the quality requirements is a key factor in the commercialization of nucleic acid drugs. The purity requirement of phosphoramidite monomers is generally ≥99.0%, and the difficulty of quality control is even higher than that of general small molecule APIs (Active pharmaceutical ingredients). It takes a long time for companies to accumulate technology to meet the quality control requirements of phosphoramidite monomers. The synthesis route of phosphoramidite monomers usually includes: (1) treating the nucleoside with acyl chloride or anhydride to add a protecting group to the base; (2) then using DMTrCl reagent to add a DMTr protecting group to the 5' to become a protected nucleoside; (3) then using a phosphorus reagent to phosphitylate the phosphoramidite monomer. Among them, the quality of the protective nucleoside directly affects the purity of the phosphoramidite monomer. Moreover, the phosphitylation reaction needs to be carried out in a water-free environment. Water will directly affect the purity and yield of the phosphoramidite monomer product. The existing protective nucleosides are mostly amorphous solid powders, which are very easy to absorb water during storage. Therefore, studying a protective nucleoside that can be stably preserved is of great significance for improving the purity and yield of the phosphoramidite monomer product. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned technical problems existing in the prior art and to provide a compound crystal form and a preparation method and application thereof.
[0004] In order to achieve the above object, the first aspect of the present invention provides a crystalline form of a compound represented by formula (1), wherein the characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystalline form include 6.94°±0.2°, 8.42°±0.2°, 9.20°±0.2°, 11.84°±0.2°, 13.00°±0.2°, 14.78°±0.2°, 15.46°±0.2°, 15.98°±0.2°, 16.76°±0.2°, 18.14°±0.2°, 19.20°±0.2°, 20.54°±0.2°, 20.94°±0.2°, 23.50°±0.2°, 25.90°±0.2°, and 26.52°±0.2°;
[0005]
[0006] The second aspect of the present invention provides a method for preparing the above-mentioned crystal form, which comprises: mixing the compound represented by formula (1) with a crystallization solvent, heating to dissolve the compound represented by formula (1), and then cooling and crystallizing to obtain the crystal form of the compound represented by formula (1); wherein the crystallization solvent is acetonitrile and / or ethyl acetate.
[0007] The third aspect of the present invention provides the use of the crystalline form of the compound represented by formula (1) described above in improving the purity of phosphoramidite monomers; more preferably, the use includes using the compound represented by formula (1) having the crystalline form described above as a raw material for synthesizing phosphoramidite monomers.
[0008] Through the above technical solution, the present invention achieves the following beneficial effects:
[0009] The purity of the nucleoside with a specific crystal form of the present invention changes slightly with the extension of the storage time, which indicates that the crystal form prepared by the method of the present invention is not easy to deteriorate and is easy to preserve.
[0010] The nucleoside with a specific crystal form of the present invention has a higher melting point and lower water content and hygroscopicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is the XRD pattern of the product prepared in Example 1. DETAILED DESCRIPTION
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0013] In a first aspect, the present invention provides a crystalline form of a compound represented by formula (1), wherein the characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystalline form include 6.94°±0.2°, 8.42°±0.2°, 9.20°±0.2°, 11.84°±0.2°, 13.00°±0.2°, 14.78°±0.2°, 15.46°±0.2°, 15.98°±0.2°, 16.76°±0.2°, 18.14°±0.2°, 19.20°±0.2°, 20.54°±0.2°, 20.94°±0.2°, 23.50°±0.2°, 25.90°±0.2°, and 26.52°±0.2°;
[0014]
[0015] According to the present invention, preferably, the characteristic peak 2θ of the X-ray powder diffraction pattern of the crystalline form also includes 5.88°±0.2°, 10.24°±0.2°, 20.06°±0.2°, 21.62°±0.2°, 22.48°±0.2°, 24.72°±0.2°, 27.26°±0.2°, 28.06°±0.2°, 28.74°±0.2°, 29.36°±0.2°, 2 9.98°±0.2°, 30.68°±0.2°, 31.28°±0.2°, 32.42°±0.2°, 34.01°±0.2°, 35.20°±0.2°, 36.48°±0.2°, 37.58°±0.2°, 38.58°±0.2°, 39.24°±0.2°, 42.60°±0.2°, 45.38°±0.2°, and 46.14°±0.2°.
[0016] According to the present invention, preferably, the structure of the compound represented by formula (1) is
[0017]
[0018] According to the present invention, preferably, the X-ray powder diffraction pattern of the crystal form is as follows Figure 1 shown.
[0019] According to the present invention, preferably, the melting point of the crystal form is 163-180°C.
[0020] According to the present invention, preferably, the content of residual solvent (acetonitrile and / or ethyl acetate) in the crystalline form is less than 3% by weight.
[0021] According to the present invention, preferably, the water content in the crystalline form is less than 1% by weight.
[0022] According to the present invention, preferably, the hygroscopicity of the crystal form is lower than 103 wt %. More preferably, the hygroscopicity of the crystal form is lower than 102 wt %. Further preferably, the hygroscopicity of the crystal form is lower than 101.7 wt %.
[0023] According to the present invention, preferably, the interplanar spacing of the crystal form is 0.15-1.6nm, and the half-peak width is 0.01-0.5nm. More preferably, the interplanar spacing of the characteristic peak of the crystal form at 2θ≤27° is 0.3-1.6nm. Further preferably, the interplanar spacing and half-peak width of the crystal form at different characteristic peaks are shown in Table 1-A,
[0024] Table 1-A
[0025]
[0026]
[0027] In the present invention,
[0028] The second aspect of the present invention provides a method for preparing the above-mentioned crystal form, which comprises: mixing the compound represented by formula (1) with a crystallization solvent, heating to dissolve the compound represented by formula (1), and then cooling and crystallizing to obtain the crystal form of the compound represented by formula (1); wherein the crystallization solvent is acetonitrile and / or ethyl acetate.
[0029] According to the present invention, preferably, the amount of the crystallization solvent used is 6-10 mL (for example, 6 mL, 6.5 mL, 7 mL, 7.5 mL, 8 mL, 8.5 mL, 9 mL, 9.5 mL, 10 mL, and a range consisting of any two of the above) per gram of the compound represented by formula (1).
[0030] According to the present invention, preferably, the heating temperature is 50-80°C (for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, and a range formed by any two of the above points).
[0031] According to the present invention, preferably, the crystallization temperature is 15-25° C., and preferably, the crystallization is performed under stirring.
[0032] According to a preferred embodiment of the present invention, when a mixed solvent of acetonitrile and ethyl acetate is used as a crystallization solvent, the heating temperature is 50-55°C and the crystallization temperature is 20-25°C. More preferably, the volume ratio of acetonitrile to ethyl acetate in the mixed solvent of acetonitrile and ethyl acetate is 0.2-0.4:1. Further preferably, the amount of the mixed solvent of acetonitrile and ethyl acetate is 6-7mL per gram of the compound represented by formula (1). When a mixed solvent of acetonitrile and ethyl acetate is used as a crystallization solvent, the crystallization time can be 8-12h.
[0033] According to a preferred embodiment of the present invention, when acetonitrile is used as the crystallization solvent, the heating temperature is 70-85°C; the crystallization temperature is 15-25°C. More preferably, the amount of acetonitrile is 8-10 mL per gram of the compound represented by formula (1). When acetonitrile is used as the crystallization solvent, the crystallization time can be 8-12 hours.
[0034] According to the present invention, preferably, the method for preparing the compound represented by formula (1) comprises: adding a solution containing dimethoxytriphenylmethane to a solution containing the compound represented by formula (II) to react, thereby obtaining the compound represented by formula (1);
[0035]
[0036] According to the present invention, preferably, the compound represented by formula (II) is
[0037]
[0038] According to the present invention, preferably, the amount of dimethoxytriphenylmethane used is 1-2 mmol per mmol of the compound represented by formula (II).
[0039] According to the present invention, preferably, the dropping temperature is 0-5°C.
[0040] According to the present invention, preferably, the dripping rate is 10-50 mL / h.
[0041] According to the present invention, preferably, the solvent in the solution containing dimethoxytriphenylmethane is at least one of pyridine and dimethylformamide; more preferably, the concentration of the solution containing dimethoxytriphenylmethane is 0.4-0.8 mol / L.
[0042] According to the present invention, preferably, the solvent in the solution containing the compound represented by formula (II) is at least one of pyridine and dimethylformamide; more preferably, the concentration of the solution containing the compound represented by formula (II) is 0.4-0.6 mol / L.
[0043] According to the present invention, preferably, the reaction conditions include: temperature of 20-25° C., and time of 10-16 h.
[0044] According to the present invention, preferably, the method for preparing the compound of formula (1) further comprises: after the reaction is completed, adding a quencher (water) to the reaction system for quenching, then extracting with dichloromethane to obtain an organic phase containing the compound of formula (II), then washing the organic phase with saturated lemon water solution, saturated sodium chloride, and saturated sodium bicarbonate, respectively, and then drying to obtain a crude product of the compound of formula (1). The purity of the compound of formula (1) (crude product) prepared by this method is 70-90%.
[0045] The third aspect of the present invention provides the use of the crystalline form of the compound represented by formula (1) described above in improving the purity of phosphoramidite monomers; more preferably, the use includes using the compound represented by formula (1) having the crystalline form described above as a raw material for synthesizing phosphoramidite monomers.
[0046] The synthetic route for preparing phosphoramidite monomers using nucleosides is as follows:
[0047]
[0048] According to the present invention, preferably, the synthesis route of the phosphoramidite monomer using the compound represented by formula (1) in the above-mentioned crystalline form is as follows:
[0049]
[0050] The present invention will be described in detail below by way of examples. In the following examples,
[0051] X-ray diffractometer conditions: the model of the instrument is Ultima IV, the manufacturer is Japan Rigaku Corporation, the voltage is 40 kV, the current is 40 mA, the scanning range (2θ): 3-90°, the step size: 0.02°.
[0052] Preparation Example 1
[0053] This preparation example is used to illustrate the method of synthesizing the compound represented by formula (1) using the compound represented by formula (II). The synthesis route is as follows:
[0054]
[0055] The compound represented by formula (II) is added to the solvent pyridine to obtain a solution containing the compound represented by formula (II) with a concentration of 0.46 mol / L. Dimethoxytriphenylmethane chloride (DMTrCl) is added to pyridine to obtain a solution containing dimethoxytriphenylmethane chloride with a concentration of 0.7 mol / L. Then, at 0-5°C, a solution containing dimethoxytriphenylchloromethane is added dropwise to a solution containing the compound represented by formula (II) at a rate of 30 mL / h. After the addition is completed, the reaction system is heated to 20-25°C for reaction for 12 hours. When the residual raw material is less than 5% as detected by HPLC, the reaction is stopped. At 0-5°C, water (the volume of water is 5 times the volume of the reaction system) is slowly added to the reaction system for quenching. Then, dichloromethane (the volume of dichloromethane is 10 times the volume of the reaction system) is added for extraction and separation. The organic phase is separated and then washed with saturated citric acid aqueous solution (the single volume of saturated citric acid aqueous solution is 5 times the volume of the organic phase) for 6 times until the TLC spot plate shows that there is no pyridine remaining in the organic phase. Then, saturated sodium chloride aqueous solution, saturated sodium bicarbonate aqueous solution and saturated sodium chloride aqueous solution are used for washing once each in turn. Then, the crude product containing the compound represented by formula (1) is obtained after drying (drying temperature is 15-25°C and drying time is 1-3 hours) and concentration. The amount of dimethoxytriphenylmethane used is 1.2 mmol per mmol of the compound represented by formula (II).
[0056] HPLC analysis showed that the purity of the crude product containing the compound represented by formula (1) was 75%.
[0057] A crude product containing the compound represented by formula (1) 1H NMR(400MHz,DMSO-d6)δ11.35(s,1H),8.52(s,1H),7.92(s,1H),7.47–7.08(m,9H), 6.82(t,J=8.8Hz,4H),6.29(t,J=6.4Hz,1H),5.37(d,J=4.4Hz,1H),4.40(q,J=5.2Hz ,1H),3.93(dq,J=9.2,5.6,4.8Hz,1H),3.73(s,6H),3.20(dd,J=10.4,6.4Hz,1H),3 .11(s,4H),3.03(s,3H),2.69(dt,J=13.2,6.4Hz,1H),2.31(dt,J=12.8,6.0Hz,1H).
[0058] Example 1
[0059] The crude product containing the compound of formula (1) obtained in Preparation Example 1 was added to a mixed solvent of acetonitrile and ethyl acetate (the amount of the mixed solvent of acetonitrile and ethyl acetate was 6.5 mL for each gram of the compound of formula (1), and the volume ratio of acetonitrile and ethyl acetate in the mixed solvent was 0.3:1), and then the temperature was raised to 50°C to completely dissolve the crude product; then the temperature was lowered to room temperature (about 20°C) and crystallized under stirring for 12 hours; then filtered and dried (drying temperature was 50°C, and drying time was 6 hours) to obtain a white crystalline product. The yield of the product was 95%. The obtained solid product was subjected to X-ray diffraction powder diffraction determination using Cu-ka rays, and the obtained XRD spectrum was as shown below. Figure 1 As shown, the XRD spectrum data is shown in Table 1-B.
[0060] Table 1-B
[0061]
[0062]
[0063] Example 2
[0064] The crude product containing the compound of formula (1) obtained in Preparation Example 1 was added to a mixed solvent of acetonitrile and ethyl acetate (the amount of the mixed solvent of acetonitrile and ethyl acetate was 7 mL for each gram of the compound of formula (1), and the volume ratio of acetonitrile and ethyl acetate in the mixed solvent was 0.4:1), and then the temperature was raised to 55°C to completely dissolve the crude product; then the temperature was lowered to room temperature (about 20°C) and crystallized under stirring for 8 hours; then filtered and dried (drying temperature was 50°C, and drying time was 6 hours) to obtain a white crystalline product. The yield of the product was 93%. The obtained solid product was subjected to X-ray diffraction powder diffraction determination using Cu-ka rays, and the data of the XRD spectrum were basically consistent with those in Example 1, which are not shown here.
[0065] Example 3
[0066] The method of Example 1 was followed, except that the mixed solvent was replaced with acetonitrile, and the amount of acetonitrile was 9 mL per gram of the compound represented by formula (1); the temperature was then raised to 80°C and stirred for 2 hours; the temperature was then lowered to 25°C and crystallized under stirring for 12 hours. The yield of the product was 90%. The obtained solid product was subjected to X-ray diffraction powder diffraction determination using Cu-ka rays, and the data of the XRD spectrum were basically consistent with those of Example 1, and are not shown here.
[0067] Comparative Example 1
[0068] The crude product containing the compound of formula (1) obtained in Preparation Example 1 was dissolved in dimethylformamide (DMF) at 25°C. After complete dissolution, the solution was quickly added dropwise to water at 0-10°C. After the addition was completed, it was quickly filtered and dried (the drying temperature was 50°C and the drying time was 6h) to obtain a solid product (powder); the yield of the product was 90%. Wherein, the amount of dimethylformamide used was 2mL and the amount of water used was 10mL per gram of the compound of formula (1). The obtained solid product was subjected to X-ray diffraction powder diffraction measurement using Cu-ka rays. There was no obvious characteristic peak in the XRD spectrum, that is, the solid product was an amorphous powder.
[0069] Comparative Example 2
[0070] The method of Comparative Example 1 was followed, except that dimethylformamide (DMF) was replaced by dichloromethane, and purified water was replaced by n-heptane. Cu-ka rays were used to perform X-ray diffraction powder diffraction measurement, and there was no obvious characteristic peak in the XRD spectrum, that is, the obtained product was an amorphous (powder) solid. The yield of the product was 87%.
[0071] Test Case
[0072] The crystals obtained in the above examples and the powder solids obtained in the comparative examples were tested for melting point, water content (KF), hygroscopicity and stability.
[0073] (1) Melting point test method: The melting point was tested using a fully automatic video melting point apparatus (manufacturer: Haineng Future Instrument Technology Group Co., Ltd., model: MP470). The temperature was raised to 90°C at a heating rate of 1°C / min, and then the sample was placed in the fully automatic video melting point apparatus to test the melting point of the sample. The test results are shown in Table 2.
[0074] (2) Water content test method: The water content was tested by Coulometric Karl Fischer titration using an automatic sampler moisture analyzer (manufacturer: Shanghai Hegong Scientific Instrument Co., Ltd., model AKF-CAS6), wherein the furnace temperature was 150° C. The test results are shown in Table 2.
[0075] (3) Hygroscopicity test method: a certain mass of the sample to be tested is placed in an open bottle, and then the open bottle is placed in a constant temperature dryer, which is filled with a saturated ammonium chloride aqueous solution. After being placed at 25±1°C for 24 hours, the weight of the sample after absorbing the moisture in the constant temperature dryer is weighed. The calculation formula for hygroscopicity is: (weight of the sample after absorbing the moisture in the constant temperature dryer - weight of the sample after absorbing the moisture in the constant temperature dryer) ÷ weight of the sample after absorbing the moisture in the constant temperature dryer × 100%. The test results are shown in Table 2.
[0076] (4-1) The sample to be tested was placed under the conditions of 40±2°C and 75±5%RH (relative humidity) for 0 day (T0), 5 days (5D), 10 days (10D), one month (1M), and three months (3M), and then the purity change of the product was tested by high performance liquid chromatography (HPLC). The test results are shown in Table 3.
[0077] (4-2) The samples were placed at 50±5°C and 75±5% RH (relative humidity) for 0 day (T0), 5 days (5D), 10 days (10D), and one month (1M), and the purity of the products was tested by high performance liquid chromatography (HPLC). The test results are shown in Table 3.
[0078] Table 2
[0079] Melting point(℃) Water content (weight %) Hygroscopicity (weight %) Example 1 163-177 0.07705 101.69 Example 2 164.1-178.1 0.1078 101.35 Example 3 163.7-177.8 0.1135 101.54 Comparative Example 1 125-140.8 1.60241 104.14 Comparative Example 2 126.3-142.5 1.2037 104.48
[0080] It can be seen from Table 2 that, relative to the comparative example, the crystal form prepared by the method of the present invention has a higher melting point, and lower water content and hygroscopicity.
[0081] Table 3
[0082]
[0083] It can be seen from Table 3 that the crystal form with a specific crystal form prepared by the method of the present invention has a small change in purity as the storage time increases, indicating that the crystal form prepared by the method of the present invention is not easy to deteriorate and is easy to preserve. Compared with the amorphous nucleoside prepared in the comparative example, the nucleoside with a specific crystal form of the present invention is beneficial to improving the purity of the phosphoramidite monomer product.
[0084] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A crystalline form of a compound represented by formula (1), characterized in that: The characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystal form include 6.94°±0.2°, 8.42°±0.2°, 9.20°±0.2°, 11.84°±0.2°, 13.00°±0.2°, 14.78°±0.2°, 15.46°±0.2°, 15.98°±0.2°, 16.76°±0.2°, 18.14°±0.2°, 19.20°±0.2°, 20.54°±0.2°, 20.94°±0.2°, 23.50°±0.2°, 25.90°±0.2°, and 26.52°±0.2°; 2. The crystal form according to claim 1, wherein The characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystal form also include 5.88°±0.2°, 10.24°±0.2°, 20.06°±0.2°, 21.62°±0.2°, 22.48°±0.2°, 24.72°±0.2°, 27.26°±0.2°, 28.06°±0.2°, 28.74°±0.2°, 29.36°±0.2°, 29.98° ±0.2°, 30.68°±0.2°, 31.28°±0.2°, 32.42°±0.2°, 34.01°±0.2°, 35.20°±0.2°, 36.48°±0.2°, 37.58°±0.2°, 38.58°±0.2°, 39.24°±0.2°, 42.60°±0.2°, 45.38°±0.2°, 46.14°±0.2°; And / or, the structure of the compound represented by formula (1) is 3. The crystal form according to claim 1, wherein The X-ray powder diffraction pattern of the crystal form is shown in FIG1 .
4. The crystal form according to claim 1, wherein The melting point of the crystal form is 163-180°C.
5. A method for preparing the crystal form according to any one of claims 1 to 4, characterized in that: The method comprises: mixing the compound represented by formula (1) with a crystallization solvent, heating to dissolve the compound represented by formula (1), and then cooling to crystallize to obtain the crystal form of the compound represented by formula (1); wherein the crystallization solvent is acetonitrile and / or ethyl acetate.
6. The method according to claim 5, wherein: The amount of the crystallization solvent used is 6-10 mL per gram of the compound represented by formula (1); And / or, the heating temperature is 50-85°C; And / or, the crystallization temperature is 15-25° C., preferably, the crystallization is performed under stirring.
7. The method according to claim 5, wherein: The preparation method of the compound represented by formula (1) comprises: adding a solution containing dimethoxytriphenylmethane to a solution containing the compound represented by formula (II) to react, thereby obtaining the compound represented by formula (1); Preferably, the compound represented by formula (II) is 8. The method according to claim 7, wherein: The amount of dimethoxytriphenylmethane used is 1-2 mmol per mmol of the compound represented by formula (II); And / or, the temperature of the dropping is 0-5°C; And / or, the solvent in the solution containing dimethoxytriphenylmethane is at least one of pyridine and dimethylformamide; preferably, the concentration of the solution containing dimethoxytriphenylmethane is 0.4-0.8 mol / L; And / or, the solvent in the solution containing the compound represented by formula (II) is at least one of pyridine and dimethylformamide; preferably, the concentration of the solution containing the compound represented by formula (II) is 0.4-0.6 mol / L.
9. The method according to claim 7, wherein: The reaction conditions include: temperature of 20-25°C, time of 10-16h; And / or, the preparation method of the compound represented by formula (1) further comprises: after the reaction is completed, adding a quenching agent to the reaction system for quenching, then extracting with dichloromethane to obtain an organic phase containing the compound represented by formula (II), then washing the organic phase with saturated lemon water solution, saturated sodium chloride, and saturated sodium bicarbonate, respectively, and then drying.
10. Use of the crystalline form of the compound represented by formula (1) according to any one of claims 1 to 4 in improving the purity of phosphoramidite monomers; preferably, the use comprises using the compound represented by formula (1) having the crystalline form described in any one of claims 1 to 4 as a raw material for synthesizing phosphoramidite monomers.